2019
DOI: 10.1186/s12888-019-2084-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between provider communication and personal recovery outcomes

Abstract: Background This study examined whether two types of provider communication considered important to quality of care (i.e., shows respect and explains understandably) are associated with mental health outcomes related to personal recovery (i.e., connectedness, hope, internalized stigma, life satisfaction, and empowerment). This study also tested whether these associations varied by the type of provider seen (i.e., mental health professional versus general medical doctor). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…Communication with professionals appeared as one of the recovery-promoting factors. A previous study showed that providers' respectful communication was associated with personal recovery from mental health problems [43]. Respectful communication may play a key role in facilitating personal recovery through avenues such as empowerment and hope/con dence.…”
Section: Professionals' Respectful Communicationmentioning
confidence: 94%
“…Communication with professionals appeared as one of the recovery-promoting factors. A previous study showed that providers' respectful communication was associated with personal recovery from mental health problems [43]. Respectful communication may play a key role in facilitating personal recovery through avenues such as empowerment and hope/con dence.…”
Section: Professionals' Respectful Communicationmentioning
confidence: 94%
“…MEASURING WHAT MATTERS FOR PEOPLE-CENTRED HEALTH SYSTEMS mean change (not shown) was +23 on the Oxford scale and +32 on the HOOS-PS scale, which equates to about 48% and 32% improvement respectively. 11 More condition-specific results are provided in Chapter 6.…”
Section: On Average Hip Replacement Patients Reported Improvementmentioning
confidence: 99%
“…(3), maladies coronariennes (4), hypertension (5), AVC et conséquences chroniques (6), arthrose, lombalgie (7), cervicalgie (8), diabète (9), allergies (10), cirrhose du foie (11), incontinence urinaire (12), problèmes rénaux (13) et dépression (14).…”
Section: Définition Et Comparabilitéunclassified